Analysis of the Influence of Local Own Revenue and General Allocation Funds on Capital Expenditure in West Nusa Tenggara Province in 2012-2021 - Firmansyah, Firmansyah; Iwan Harsono; Endang Astuti (Experimental Student Experiences, 2023)
This study aims to determine the effect of Regional Native Income and General Allocation Fund on Capital Expenditure in West Nusa Tenggara Province in 2012-2021. The type of research used is quantitative research that emphasizes analysis of data with statistical methods. The data collection technique in this study is to use observation and documentation. The data analysis technique used is multiple regression analysis. This study took data on the report on the realization of local original income, general allocation funds and annual capital expenditures at the Central Statistics Agency of West Nusa Tenggara Province during the 2012-2021 period. The results of this study indicate that Regional Own Revenue and General Allocation Fund partially have no significant effect on Capital Expenditure. Simultaneous testing shows that Regional Own Revenue and General Allocation Funds do not have a significant effect on Capital Expenditure.